Xenophobic Violence and Struggle Discourse in South Africa. (November 2019) - Kerr, Philippa; Durrheim, Kevin; Dixon, John
This paper argues that xenophobia in South Africa is entangled in discourses of liberation struggle, which are often used to justify anti-foreigner violence. We first examine some existing academic explanations for xenophobia, namely internalised racism, poverty/inequality, nationalism, and township and informal settlement politics. To avoid deterministically explaining xenophobia as 'caused' by any of these factors, however, we introduce a concept from social psychology, the concept of 'working models of contact'. These are common frames of reference in which contact between groups is understood in terms of shared meanings and values. Xenophobic violence is not caused but instantiated in ways that are explained and justified according to particular understandings of the meaning of the 'citizen-foreigner' relationship. We then review three case studies of xenophobic violence whose perpetrators constructed a model of contact in which African 'foreigners' were undermining the struggles of South Africans in various socio-economic contexts. We also examine three cases where xenophobic violence was actively discouraged by invoking an inclusive rather than divisive form of struggle discourse. Thus the nature of the struggle itself becomes contested. We conclude by considering some dilemmatic implications that our analysis provokes.